Habitat Selection by American Martens in Coastal California - SLAUSON, KEITH M.; ZIELINSKI, WILLIAM J.; HAYES, JOHN P. (The Journal of Wildlife Management, 2007)
ABSTRACT We investigated habitat selection using single‐ and mixed‐scale modeling at 2 spatial scales, stand and home range, by the only known population of American martens ( Martes americana ) remaining in the historical range of the Humboldt subspecies ( M. a. humboldtensis ) in California, USA. During 2000 and 2001, we sampled a 12 times 14 grid with 2‐km spacing, using 2 sooted track plates at each grid point. We detected martens at 26 of the 159 grid points. We used resource selection probability functions and an information‐theoretic method to model habitat at detection locations. At the stand scale, martens selected conifer‐dominated stands with dense, spatially extensive shrub cover (x̄ = 74% cover, SE = 4) in the oldest developmental stage. At the home‐range scale, martens selected the largest available patches (x̄ = 181 ha, SE = 14) of old‐growth, old‐growth and late‐mature, or serpentine habitat. Mixed‐scale models revealed that habitat characteristics from both scales best explained marten occurrence compared to one scale alone. Dense, spatially extensive shrub cover is a key habitat element for martens in coastal forests. Dense shrubs provide refuge from predators, cover for prey, and may also deter larger‐bodied competitors. Managers can increase the likelihood of marten population persistence and encourage expansion in coastal forests by maintaining and restoring late‐mature and old‐growth, conifer‐dominated forests with dense shrub cover in large, contiguous patches.